PENDAMPINGAN PEMASARAN BERBASIS MEDIA SOSIAL HASIL OLAHAN BUNGA ROSELA ( HIBISCUS SABDARIFFA L) HOME INDUSTRI IBU SAM DUSUN 1 PEKON AMBARAWA TIMUR SEBAGAI BAHAN UTAMA TEH TRADISIONAL BAGI MASYARAKAT (LP3K Lampung, 2022)
One of the impacts of the COVID-19 pandemic is that business people find it difficult to market their products, especially brands that have been built previously become unknown again because the government has imposed large-scale social restrictions (PSBB) and social distancing to suppress positive growth rates. During a pandemic like this, people are encouraged to adopt a healthy lifestyle. People are encouraged to eat and drink healthy, such as herbal drinks processed by the rosella plant. By being required to stay at home, a social media account was created to make it easier for producers to market their products, and for consumers to easily find processed rosella flowers.